Avian Influenza Scare and Poultry Egg Production in Uyo Urban, Nigeria - Akpabio, I.A.; Okon, D.P.; Angba, A.O.; Aboh, C.L. (International Journal of Poultry Science, 2007)
The study attempted to analyze in comparative terms, the poultry egg production enterprise in Uyo urban of Akwa Ibom State, Nigeria. Focus was on the socio-economic characteristics of poultry producers and constraint affecting the enterprise. The study reference was to the pre and post avian flu scare period in the country. Findings revealed functional changes in the socio-economic characteristics of poultry egg producers, while the constraint factors are more intense in the post-avian flu period. Recommendations are proffered to ameliorate the situation.